TRANSFORMATION OF CARVING LEARNING: A STUDY ON THE UTILIZATION OF DIGITAL MEDIA AS A SOURCE OF ADAPTIVE LEARNING FOR THE YOUNG GENERATION OF CARVERS IN JEPARA - Kurniawan, Bambang Kartono; Hapiz, Hana Yazmeen; Abdullah, Muhamad Ezran Zainal (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
The Jepara carved furniture industry in Indonesia has historically relied on the transmission of cultural knowledge between generations through Nyantrik, a traditional apprenticeship system. However, shifting socio-cultural contexts and the increasing accessibility of digital technologies have changed the way young generations acquire and develop carving skills. This study examines the transformation of carving learning by analysing the integration of digital media as an adaptive learning resource. Using a sequential exploration mixed method design, this study investigated the attitudes of young artisans and assessed their readiness to adopt digital tools. The research findings show how technology exposure is mediated by adaptive capacity to produce a hybrid of traditional innovation and continuity. Quantitative analysis using One-Way ANOVA revealed significant differences in perceptions of design evolution among sculptors, entrepreneurs, and designers [F (2, 154) = 15.42, p < 0.001], but identified an integrated commitment to adaptive strategies. The study concluded that effective use of digital media, when combined with guidance from senior carvers, is essential to sustain Jepara’s carving industry. This research contributes a theoretical framework for heritage preservation in the digital age, offering a foundation for integrating modern pedagogy with local wisdom.